Dynamic tensile behavior of steel strands at different strain rates. (October 2021) - Xing, Xinkui; Lin, Lanri; Qin, Heying
Abstract: In engineering structures, steel strands can be subjected to dynamic loads associated with earthquakes, vehicle impacts, explosions and other special circumstances occurring in addition to static loads and resulting in higher strain rates. Therefore, it is of great significance to study the mechanical performance of steel strands subjected to dynamic loads at high strain rates. In this study, first an electrohydraulic high-speed impact test system, an electrohydraulic servo shear-stress test system, and a universal testing machine were used to conduct the dynamic tensile tests on single-wire, single-bundle, and four-bundle steel strands at ten different strain rates (2.73 × 10 −3 –10.714 s −1 ), and the influences of the strain rate and strand diameter on the mechanical behavior of steel strands were analyzed based on the experimental data. At the same time, the wire breakage, failure modes, and fracture forms were analyzed, and the Ramberg-Osgood and Johnson-Cook constitutive models were revised to obtain a constitutive relationship which, along with the related material parameters, better describes the stress–strain behavior of the tensile steel strands subjected to dynamic tensile loads. The results show that the steel strands are clearly sensitive to strain rate, which is higher in quasi-static states and at low strain rates. At higher strain rates, the sensitivity to strain rate decreases, and the sensitivity of yield strength is higher than the ultimate strength. The strand diameter has certain influence on the steel strands performance. The ultimate strains of the single-wire and four-bundle steel strands are all smaller than that of the single-bundle steel strands. Twisting of the single-bundle steel strands weakened the wires and resulted in premature wire breakage. The failure modes of steel strands subjected to different tensile strain rates shifted from ductile to brittle. The failure modes were mainly of three types, namely, necking-milling, splitting-milling, and splitting. The Ramberg-Osgood and the Johnson-Cook constitutive models with the Cowper-Symonds strain rate parameter correction can more accurately reflect the variation in the strain hardening characteristics of steel strands with strain rate.